System Design and Experimental Study of a Four-Roll Bending Machine - Dongxu Guo; Qun Sun; Ying Zhao; Shangsheng Jiang; Yigang Jing (Applied Sciences)
This study addresses the urgent demand for high-precision manufacturing of curved components by developing a fully servo-driven multi-axis controlled four-roll bending machine. By integrating a modular symmetric roller system design with a distributed hierarchical motion control architecture, we achieved substantial enhancements in scalability, forming stability, and machining accuracy. The mechanical system underwent static simulation optimization using SolidWorks Simulation, ensuring maximum stress in the guiding mechanism was controlled below <semantics>7.118×103</semantics> N/m². ABAQUS-based roll-bending dynamic simulations validated the geometric adaptability and process feasibility of the proposed mechanical configuration. A master-slave dual-core control architecture was implemented in the control system, enabling synchronized error ≤ 0.05 mm, dynamic response time ≤ 10 ms, and positioning accuracy of ±0.01 mm through collaborative control of the master controller and servo drives. Experimental validation demonstrated that the machine achieves bending errors within 1%, with an average forming error of 0.798% across various radii profiles. The arc integrity significantly outperforms conventional equipment, while residual straight edge length was reduced by 86.67%. By adopting fully servo-electric cylinder actuation and integrating a C#-developed human–machine interface with real-time feedback control, this research effectively enhances roll-bending precision, minimizes residual straight edges, and exhibits broad industrial applicability.